Charge Transport Through Split Photoelectrodes in Dye-sensitized Solar Cells - Fakharuddin, Azhar; Irfan, Ahmed; Zulkeflee, Kalidin; M. M., Yusoff; Rajan, Jose (AIP Publishing LLC., 2014)
Charge transport and recombination are relatively ignored parameters while upscaling dye-sensitized solar cells (DSCs). Enhanced photovoltaic parameters are anticipated by merely widening the devices physical dimensions, viz., thickness and area as evident from the device design adopted in reported large area DSCs. These strip designs lead to ≤50% loss in photocurrent compared to the high efficiency lab scale devices. Herein, we report that the key to achieving higher current density (JSC ) is optimized diffusion volume rather than the increased photoelectrode area because kinetics of the devices is strongly influenced by the varied choices of diffusion pathways upon increasing the electrode area. For a given electrode area and thickness, we altered the photoelectrode design by splitting the electrode into multiple fractions to restrict the electron diffusion pathways. We observed a correlation between the device physical dimensions and its charge collection efficiency via current-voltage and impedance spectroscopy measurements. The modified electrode designs showed >50% increased JSC due to shorter transport time, higher recombination resistance and enhanced charge collection efficiency compared to the conventional ones despite their similar active volume (∼3.36 × 10−4 cm3). A detailed charge transport characteristic of the split devices and their comparison with single electrode configuration is described in this article.